Current Status of Polymers Based on Organosilicon Compounds - Rosilov Mansur Sirgiyevich; Ergashev Yusuf To’ra o’gli (Research Parks Publishing LLC, 2022)
Polyvinyl chloride (PVC) is one of the most bulky polymers produced both in Russia and abroad. The production of PVC and products based on it has been established at more than 100 enterprises in 50 countries around the world. In recent years, significant progress has been made in the production of PVC and products from it: pipes, profiles, including window films, sheets, PVC products.